Techniques, materials and resources used in the art therapeutical process - López Martínez, Mª Dolores (Arteterapia. Papeles de arteterapia y educación artística para la inclusión social, 2012)
The distinctive features of Art therapy are represented in the combination of the artistic expression and the therapeutic process. In this relation, the tools are the different plastic and visual art techniques and materials as a vehicle that makes possible the communication between patient and arttherapist. The use of these means causes to consider them in two of their essencial facets: in its psychological dimension affecting its comunicative, expressive and symbolic potencial and in its material dimension, emphasizing its possibilities and material qualities.
Keywords: Art therapy; art-therapeutic process; plastics and visuals techniques and materials; psychological dimension; material dimension.